2018
DOI: 10.1039/c8gc00828k
|View full text |Cite
|
Sign up to set email alerts
|

Insight into effective denitrification and desulfurization of liquid fuel with deep eutectic solvents: an innovative evaluation criterion to filtrate extractants using the compatibility index

Abstract: The compatibility index (CI and PCI) as a new criterion is feasible to evaluate the removal efficiency of heterocycles in green and economic DESs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…In general, sulfur compounds are the hardest to be removed, with Th exhibiting the lowest extraction efficiencies for all extraction systems tested. This trend was also observed by several authors, who extracted both sulfur and nitrogen compounds with ILs and more recently also with different DES . In this context, Li et al pointed out the fact that the low polarity of the sulfur compounds is the most likely explanation for this difficulty in extracting sulfur compounds, since all of the DES studied in this work are composed of salts and thus charged.…”
Section: Resultssupporting
confidence: 83%
“…In general, sulfur compounds are the hardest to be removed, with Th exhibiting the lowest extraction efficiencies for all extraction systems tested. This trend was also observed by several authors, who extracted both sulfur and nitrogen compounds with ILs and more recently also with different DES . In this context, Li et al pointed out the fact that the low polarity of the sulfur compounds is the most likely explanation for this difficulty in extracting sulfur compounds, since all of the DES studied in this work are composed of salts and thus charged.…”
Section: Resultssupporting
confidence: 83%
“…Currently, we are studying dye removal tests from water with eutecto gels (Figure S2), on the grounds of the good results observed with ionogels . However, these materials will also be tested in the near future as a sorbent system for removal of sulfur compound from fuels or the adsorption of atmospheric pollutants, like ammonia, toward which DES have already proven very efficient. , …”
Section: Discussionmentioning
confidence: 99%
“…34 However, these materials will also be tested in the near future as a sorbent system for removal of sulfur compound from fuels or the adsorption of atmospheric pollutants, like ammonia, toward which DES have already proven very efficient. 6,35 ■ ASSOCIATED CONTENT * S Supporting Information…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption capacity of IL when applied to the mixed model fuel (S+N compounds) is much lower comparedto the pure S or pure N model compounds. The other research by Banisharif [87] [243] reported thatcholine chloridebased DESs (Deep eutectic solvents) for extractive and extractiveoxidative DS and DN of model and real fuels. Authors choosen several types of DES: as hydrogen bond acceptorcholine chloride (ChCl), and as hydrogen bond donor pmethylphenylacetic acid, mandelic acid, p toluenesulfonic acid, 1,3propylene glycol, malonic acid, urea, L(+)tartaric acid.…”
Section: Simultaneous Removal Of Organosulfur and Organonitrogen Compmentioning
confidence: 99%